The nexus between greenhouse gas emissions and food security in sub-Saharan Africa: A system GMM analysis - Yezihalem Mebrie Gobezie; Jonse Bane Boka (Cogent Economics & Finance, 2023)
In SSA, evidence is scanty on the association between greenhouse gas emissions and food security, though the region is highly vulnerable to climate change. Thus, this study has examined the effects of greenhouse gas emissions on food security in 22 SSA countries for the period 2005-2018. We employed a one-step system GMM to control for endogeneity and individual heterogeneity problems. The GMM was also an efficient estimator for a dynamic panel data model. Results of the study revealed that most SSA countries are in the vicious circle of food insecurity, with very limited improvement over the study period. In addition, the GMM result found that the accumulation of greenhouse gases has significantly contributed to reduction of food security in SSA. Greenhouse gas emissions have a negative and statistically significant effect on food security. A 1% increase in greenhouse gas emissions has resulted in a 1.2% decrease in food security. However, livestock production, agricultural employment, and economic growth have improved food security, though livestock production and economic growth have very low significant coefficients. Therefore, the study recommends that the region should devote an immense effort to boost food security through combating greenhouse gas emissions and achieving the net-zero emission target of SDG 13 on climate change. Policy makers and governments should also consider policy interventions like providing funding to assist green projects and sustainable agricultural practices to reduce the negative effects of climate change.
Keywords: 330; food security index; Greenhouse gas emissions; SSA; system GMM